Pengaruh Sistem Informasi Akuntansi, Motivasi Kerja, dan Budaya Organisasi Terhadap Kinerja Karyawan (Studi Kasus Pada PT Hardo Soloplast Karanganyar) - Iqbal Zaidan Yasykur; Dul Muid (JEMAP, 2023)
This study aims to determine the influence of accounting information systems, work motivation, and organizational culture on employee performance, especially at PT Hardo Soloplast Karanganyar. The source and type of data in this study were primary data obtained by questionnaires distributed to 100 respondents. The data sampling technique was purposive sampling. This research gathers employees at PT Hardo Soloplast Karanganyar who are qualified to be still actively working. Data processing is done using SPSS. The results of this study show that accounting information systems, work motivation, and organizational culture have a positive effect on employee performance